Covalent labeling of a chromatin reader domain using proximity-reactive cyclic peptides. Issue 22 (19th May 2022) - Zhang, Meng Yao; Yang, Hyunjun; Ortiz, Gloria; Trnka, Michael J.; Petronikolou, Nektaria; Burlingame, Alma L.; DeGrado, William F.; Fujimori, Danica Galonić
Abstract : We describe the development of covalent cyclic peptide ligands which target a chromatin methylation reader domain using a proximity-reactive sulfonyl fluoride moiety. Abstract : Chemical probes for chromatin reader proteins are valuable tools for investigating epigenetic regulatory mechanisms and evaluating whether the target of interest holds therapeutic potential. Developing potent inhibitors for the plant homeodomain (PHD) family of methylation readers remains a difficult task due to the charged, shallow and extended nature of the histone binding site that precludes effective engagement of conventional small molecules. Herein, we describe the development of novel proximity-reactive cyclopeptide inhibitors for PHD3—a trimethyllysine reader domain of histone demethylase KDM5A. Guided by the PHD3–histone co-crystal structure, we designed a sidechain-to-sidechain linking strategy to improve peptide proteolytic stability whilst maintaining binding affinity. We have developed an operationally simple solid-phase macrocyclization pathway, capitalizing on the inherent reactivity of the dimethyllysine ε-amino group to generate scaffolds bearing charged tetraalkylammonium functionalities that effectively engage the shallow aromatic 'groove' of PHD3. Leveraging a surface-exposed lysine residue on PHD3 adjacent to the ligand binding site, cyclic peptides were rendered covalent through installation of an arylsulfonyl fluoride warhead. The resulting lysine-reactive cyclic peptides demonstrated rapid and efficient labeling of the PHD3 domain in HEK293T lysates, showcasing the feasibility of employing proximity-induced reactivity for covalent labeling of this challenging family of reader domains.